"A Simple Act of Justice": The Pueblo Rejection of U.S. Citizenship in the Early Twentieth Century. (October 2022) - Teeters, Lila M.
Abstract: In January of 1920, the House of Representatives passed HR 288, also known as the Carter Bill, which would have made all American Indians born in the territorial United States citizens. While lauded by some as a "simple act of justice" to extend citizenship to America's first peoples, many Native Americans protested the bill, which eventually led to its demise. In the press, the Pueblos led the protest. Their activism highlights key, yet overlooked, developments in American Indian citizenship in the early twentieth century. First, citizenship lost any pretense of a consensual nature. Second, Indigenous protests forced congressmen to change the very nature of citizenship: from a status that marked completed assimilation to something much more pluralistic. Highlighting the Pueblos' fight helps historians analyze Native activism in the Progressive Era while problematizing citizenship as the ultimate aspirational status.